Missed Opportunities in the Early Response to COVID-19 in Aceh Province: January to May 2020 - Sofyan Sufri; Nurhasanah Nurhasanah; Nurhayati Nurhayati; Munazar Munazar; Ainal Mardhiah; Hermansyah Hermansyah; Saiful Bakri; Misbahul Jannah; Febi Dwirahmadi; Shannon Rutherford (International Journal of Disaster Management, 2021)
Coronavirus Disease (COVID-19) pandemic has had catastrophic health and economic impacts worldwide. As of 20 September 2020, Indonesia ranked the third highest of fatalities due to COVID-19 infection in Asia and the second highest of confirmed cases in Southeast Asia.  Aceh, a province in the westernmost of the country, has also been impacted by the virus infections.This study aims to investigate the current Central and Aceh provincial government-led responses to COVID-19 pandemic from January to May 2020. It utilises existing regulations, official reports and relevant websites in order to assess and analyse the responses. The findings identify delayed early responses taken by Central and Aceh governments to stop and prevent the virus transmission; the absence of lockdown implementation (border restrictions at entry points such as borderland areas, seaports and airports); premature introduction of the new normal era; the absence of checkpoints and village alert teams throughout 23 districts; and inadequate enforcement of the established regulations to halt the spread of the virus in the province.Various recommendations are provided to enhance the current responses to COVID-19 in the province in order to reduce the pandemic risk to the community going forward, and strengthen the pandemic preparedness and response system.